Etika Konsumsi Dalam Perspektif Maqāṣid Al-Sharī’ah - Yasmin, Aulia Syafitri; Alifatuhzzahra, Nisa; Sari, Cut Dila; Setyany, Henny; Amelia, Rizqa (Economic Reviews Journal, 2024)
The purpose of this study is to find out how consumption ethics in Islam are based on the review of maqāṣid alsharī’a. The method used in this paper is the library method. Based on the results of the study note that ethics in Islam is part of maqāṣid al-sharī’a. The consumption ethics in Islam is no israf and tabdzir, don’t eat food that is forbidden by Allah SWT. The purpose of don’t allowing Israf and tabdzir, don’t eat food and drink that is forbidden, is an effort to safeguard the human soul and reason. Kata kunci: Consumption; Ethics; Maqāṣid al-Sharī’a.